واقع إدارة الجودة الشاملة بجامعة أحمد دراية - أدرار - بن العارية، حسين Bin Alariah, Hussein; محجوبى، زينب Mahjoubi, Zainab; عبدالقادر، عبدالرحمان (جامعة عاشور زيان الجلفة - كلية العلوم الاقتصادية والعلوم التجارية وعلوم التسيير, 2017)
The quality of education of the big challenges faced by all educational institutions and in particular the University of them, which prompted many of them to adopt a total quality management concepts in order to raise the level of teaching and learning and a focus on the quality of its output efficiency. Therefore, this study aims to examine the reality of the comprehensive quality management at the University of Adrar, has been studying the views of professors and students of the university these circumstances, and in light of that study concluded that there is no comprehensive quality at the level of this university.
تعد جودة التعليم من التحديات الكبيرة التي تواجهها جميع المؤسسات التعليمية وبالخصوص الجامعية منها، الأمر الذي دفع بالعديد منها لتبني مفاهيم إدارة الجودة الشملة بهدف رفع مستوى التعليم والتعلم والتركيز على الكفاءة النوعية لمخرجاته. لذلك تهدف هذه الدراسة إلى دراسة واقع إدارة الجودة الشاملة بجامعة ادرار، وقد تم دراسة آراء أساتذة وطلبة هاته الجامعة، وعلى ضوء ذلك توصلت الدراسة إلى أنه ليس هناك جودة شاملة على مستوى هذه الجامعة.
Keywords: إدارة الجودة الشاملة -- التعليم العالي -- جودة التعليم -- الجزائر -- جامعة أدرار -- المؤسسات التعليمية -- جودة المخرجات